A discourse on the Persian Chahar-Bagh as an Islamic garden - Abdul Latiff, Zainab; Mohd Yunos, Mohd Yazid; Mohd Yaman, Maheran (Malaysian Institute of Planners, 2017)
The ancient garden plan, the Chahar-Bagh, was originally put onto ground for the purpose of organizing garden in an arid landscape of Persia besides a symbol of political territory. This quadripartite plan of garden was found as early as 600 BC during Achaemenid era. Therefore, claims made in various scholarships that referred Chahar-Bagh as an Islamic garden basic pattern is apparently deceiving the true meaning of Islam, which came into the world in seventh century. The method of content analysis and library search that emphasized on the theories and principles of Persian garden have been adopted in this study. To conclude, Chahar-Bagh pattern preceded Islam therefore, assigning it as the basic pattern of Islamic garden planning and design is irrelevant.